The Hours = Las Horas : visual arts of contemporary Latin America = artes visuales de Ameérica Latina contemporanea - Daros-Latinamerica AG, Zürich (Zürich : Daros-Latinamerica AG Zürich, 2005)
Bruguera, Tania ; Caldas, Waltercio ; Cardoso, Maria Fernanda ; Carpinteros, Los ; Costantino, Nicola ; Diaz, Gonzalo ; Echavarria, Juan Manuel ; Escobar, Dario ; Ferrari, León ; Jaar, Alfredo ; Kuitca, Guillermo ; Macià, Oswaldo ; Marcaccio, Fabian ; Monge, Priscilla ; Muniz, Vik ; Munoz, Oscar ; Neto, Ernesto ; Ospina, Nadin ; Perez Bravo, Marta Maria ; Pina, Manuel ; Porter, Liliana ; Prieto, Wilfredo ; Rennó, Rosângela ; Restrepo, José Alejandro ; Romero, Betsabeé ; Saavedra, Lázaro ; Salcedo, Doris ; Sántiz Gómez, Maruch ; Sastre, Martin ; Sierra, Santiago
biog., ind. tent., gr. tent., bibliog. per kunstenaar
Engels, Spaans
Exhibition. The Hours : Visual Arts of Contemporary Latin America. Daros-Latinamerica AG Zürich. 2005-10-05. 2006-01-15
boek